1991
DOI: 10.1113/jphysiol.1991.sp018435
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic secretion of quanta from nerve terminals in toad (Bufo marinus) muscle modulated by adenosine.

Abstract: SUMMARY1. A study has been made of the effect of blocking endogenous adenosine on the statistics of quantal secretion at nerve terminals in toad (Bufo marinus) muscle, during summer and winter.2. Exogenous adenosine (10-50,M) reduces the mean quantal content of the endplate potential (EPP) recorded with an intracellular microelectrode (m) by 36 + 6 % (mean + S.E.M.), independent of the control value of m in both summer and winter. The variance of the EPP (S2) was reduced by adenosine in proportion to in-, so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
(45 reference statements)
3
16
0
Order By: Relevance
“…Since these measurements were made at full quantal content to maximize the endogenous release of adenosine, it is difficult to determine the precise effect of endogenous adenosine on quantal content. However, based on the finding that adenosine has no effect on postsynaptic sensitivity (see Bennett, Karunanithi & Lavidis, 1991), and assuming that the average frog motor nerve terminal releases about 200 quanta, we estimate that endogenous adenosine reduces acetylcholine release by about twenty to forty quanta.…”
Section: Effects Of Endogenous Adenosinementioning
confidence: 98%
“…Since these measurements were made at full quantal content to maximize the endogenous release of adenosine, it is difficult to determine the precise effect of endogenous adenosine on quantal content. However, based on the finding that adenosine has no effect on postsynaptic sensitivity (see Bennett, Karunanithi & Lavidis, 1991), and assuming that the average frog motor nerve terminal releases about 200 quanta, we estimate that endogenous adenosine reduces acetylcholine release by about twenty to forty quanta.…”
Section: Effects Of Endogenous Adenosinementioning
confidence: 98%
“…At motor nerve endings, adenosine derivatives are released together with ACh (Silinsky, 1975;Smith & Lu, 1991) and act via adenosine receptors at the extracellular surface of the nerve ending as negative feedback modulators of ACh release (Ginsborg & Hirst, 1972; Silinsky, 1980;Ribeiro & Sebastiaa, 1987; Bennett, Karunanithi & Lavidis, 1991). Despite the suggestions that adenosine derivatives may be responsible for presynaptic neuromuscular depression (Silinsky, 1975;Meriney & Grinnell, 1991), the specific target site for the inhibitory effect of adenosine on transmitter release is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent theoretical analysis has shown that such non-uniformity does not reduce the variance of secretion so that binomial statistics apply; rather the process could be explained if a co-transmitter is released with the acetylcholine quantum following a nerve impulse and this co-transmitter then acts on the terminal to inhibit secretion from adjacent release sites (Bennett & Robinson, 1990). In a previous paper (Bennett, Karunanithi & Lavidis, 1991) it was shown that a candidate for this autoinhibitory process is adenosine, either derived from the secretion of its nucleotide triphosphate (ATP) or directly from endogenous stores at the synaptic site (Sebastiao & Ribeiro, 1985;Ribeiro & Sebastiao, 1987; for a review see Ribeiro & Sebastiao, 1986). Adenosine decreases quantal secretion at neuromuscular synapses (Ginsborg & Hirst, 1972;Silinksy, 1984; for a review see Jones, 1987) and decreases the variance of the secretion (Bennett et al 1991) before being inactivated by uptake (Ribeiro & Sebastiao, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper (Bennett, Karunanithi & Lavidis, 1991) it was shown that a candidate for this autoinhibitory process is adenosine, either derived from the secretion of its nucleotide triphosphate (ATP) or directly from endogenous stores at the synaptic site (Sebastiao & Ribeiro, 1985;Ribeiro & Sebastiao, 1987; for a review see Ribeiro & Sebastiao, 1986). Adenosine decreases quantal secretion at neuromuscular synapses (Ginsborg & Hirst, 1972;Silinksy, 1984; for a review see Jones, 1987) and decreases the variance of the secretion (Bennett et al 1991) before being inactivated by uptake (Ribeiro & Sebastiao, 1987). The question arises as to how adenosine exerts its effects at synapses which secrete acetylcholine.…”
Section: Introductionmentioning
confidence: 99%